Improvement of symptoms in patients with sick sinus syndrome by spontaneous development of stable atrial fibrillation. Issue 2 (February 1977) - Vera, Z; Mason, D T; Awan, N A; Miller, R R; Janzen, D; Tonkon, M J; Vismara, L A
Abstract : Fifty-six patients with symptomatic chronic sinus bradycardia because of sick sinus syndrome (SSS) were followed for periods from one month to 11 years (average 3-2 years). Eleven developed stable atrial fibrillation persisting for 8 to 61 months; 52 had permanent demand pacemakers implanted before atrial fibrillation commenced. In the 11 patients with atrial fibrillation, 10 had adequate ventricular rate, 8 with rates greater than 100 beats/min requiring digoxin for rate control. The 8 patients with atrial fibrillation with pacemakers remained asymptomatic for 13 to 18 months without requiring reimplantation; battery failure occurred in 2 whose rapid ventricular rates were controlled by digoxin. In the other 6 patients with pacemakers who developed atrial fibrillation, adequate ventricular rates persisted resulting in overdrive suppression. No patient had systemic embolisation. The previous duration of symptomatic sinus bradycardia was longer in patients developing atrial fibrillation (average 5-5 years) compared (P less than 0-01) with patients without atrial fibrillation (1-9 years). Further, premature atrial contractions occurred in all 11 patients before atrial fibrillation in contrast to only 21 of the 45 patients without atrial fibrillation. It is concluded that occurrence of atrial fibrillation in SSS with symptomatic sinus bradycardia provides a natural cure of symptoms caused by bradycardia. These data indicate that permanent ventricular pacing may not be necessary if persistent atrial fibrillation develops in SSS.